2018
DOI: 10.3390/bs8040038
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Title IX Coordinators on College and University Campuses

Abstract: The purpose of this study was to better understand the role of Title IX coordinators and their policies across four-year universities and two-year community colleges in the United States (U.S.). There is little information regarding Title IX coordinators’ training, background, and policies on how they handle Title IX investigations regarding sexual violence. The data come from an online survey that included 692 Title IX coordinators across four-year (private and public) and two-year campuses and represented 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Not getting enough money from home makes young people rate the level of support from their family as inadequate. Adequate family support means young people are not at the mercy of in uential men who often lure vulnerable girls with material and monetary gifts, which increases the risk of exposure to sexual violence [16,17]. Our nding and explanation is consistent with previous studies that have established the link between poverty and sexual violence [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Not getting enough money from home makes young people rate the level of support from their family as inadequate. Adequate family support means young people are not at the mercy of in uential men who often lure vulnerable girls with material and monetary gifts, which increases the risk of exposure to sexual violence [16,17]. Our nding and explanation is consistent with previous studies that have established the link between poverty and sexual violence [49][50][51].…”
Section: Discussionsupporting
confidence: 89%
“…The independent variables included are demographic characteristics, such as age and parity, family factors such as family structure, living with parents and family support, and behavioural factors such as smoking tobacco products and alcohol and drug use. The selected variables are based on our review of the previous studies [4,16,17]. Age was measured as a continuous variable but later categorised as 19 years or less and 20-24 years.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, campuses should also continue to increase their campus climate surveys, and make these data available to the public, so that it might increase awareness for students and their parents. A recent study [33] found that only half of Title IX coordinators had completed a campus climate survey, thus there is a lack of knowledge on the part of schools when they fail to survey their students. Increasing awareness may provide new practical insights that could shape decisions made by campus officials, healthcare workers, and reporting structures.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only 16% of campuses in 2014 had conducted an annual campus climate survey (McCaskill, 2014), and many use different measures making cross-campus comparisons challenging. However, in 2017, the majority (57%) of campuses reported that they had completed a campus climate survey, whereas 28% were in the planning stages, and 15% had not completed a survey (Wiersma-Mosley & DiLoreto, 2018). Schools that rely strictly on victim reporting such as Clery data, as some schools do, likely get relatively few reports in comparison with the sexual violence actually occurring (Cantalupo, 2014).…”
Section: Resultsmentioning
confidence: 99%